Instituto Santa Catarina de Sena: incursões educativas na formação de meninas em Belém do Pará (1903 - 1960) - OLIVEIRA, Camilla Vanessa Chagas Peixoto de (Universidade Federal do Pará, 2017)
This study talks about the socio-educational history of the Saint Catarina Institute of Sena in the period 1903-1960. Institution founded in 1909 by Italian missionaries belonging to the congregation of the Sisters of the poor of Saint Catarina of Sena, who settled in Belém do Pará at the beginning of the twentieh century with the aim of attending to poor childhood and helpless them of Pará place, Diverse non-attendance of other socioeconomic classes, since a capital of Pará was lacking of religious institutions to this clientele. In this way, it is understood as educational practices developed in the institute and a demystification of the schooling of girls living in the city of Belém through religious educational practices. The historic time adopted in this study was the years 1903-1960, which portrays the foundation of the institute and its enlargements. Thus, the guiding questions of this research are: What social and educational actions were developed at the Saint Catarina Institute of Sena, in Belém do Pará, from 1903 to 1960? What is the importance of the symbolic figure of Saint Catarina for the foundation of the congregation of the religious order of the Sisters of the Poor of Saint Catarina de Sena? What is the school culture of the educational proposal of the Saint Catarina Institute in Belém of Pará from 1903 to 1960? What are the educational practices imbricated in the Saint Catarina Institute of Sena in the formation of girls? In order to answer these questions, the main objective of this study is to verify the socio-educational actions of the Saint Catarina Institute of Sena in Belém of Pará from 1903 to 1960. Thus, from the major objective, we intend to: 1-Analyze the importance of the sign figure of Santa Catarina for the foundation of the congregation of the religious order Sisters of the Poor of Santa Catarina de Sena; 2-Investigate through the school culture the educational proposal in the Santa Catarina Institute of Sena in Belém of Pará between the years of 1903 to 1960; 3 - To examine the educational practices imbricated in the Saint Catarina Institute of Sena in the feminine formation. To do so, the corpus of the research is composed of the collection of documents, collected and selected in the school archive, such as: minutes, statute, photographs, registration books, admission books, newspaper articles, periodicals, among others. The interviews / oral narratives are used with ex-students of the institution, in order to obtain data about the education and the school context, lived according to the philosophy of the group of Italian religious. Therefore, the study will contribute to unveil the educational practices and school culture present in the Saint Catarina Institute of Sena, which is part of the History of Education in Pará.